A Study of The Quality of Life in Patients with Schizophrenia: A Cross-Sectional Study in A Tertiary Care Hospital, Mumbai, India - Prasad Tagad; Nitin Bhoge; Ivan Netto; Pritish Raut (National Journal of Community Medicine)
Background: There are limited recent Indian studies assessing the quality of life in patients with schizophrenia. This study evaluated the socio-demographic data, psychopathology, quality of life, and their associations in patients with schizophrenia.